PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU DAN KARYAWAN BIMBINGAN DAN KONSULTASI BELAJAR NURUL FIKRI WILAYAH KOTA BEKASI - Khozim; Mardisentosa, Bambang; Hardian, Dadan Eliadi (Perspektif : Jurnal Ilmu Administrasi, 2025)
This research is based on the problem of suboptimal performance of teachers and employees at the Nurul Fikri Study Guidance and Consultation in the Bekasi City Region, particularly in achieving the target number of students. The objective of this study is to analyze and empirically prove the influence of leadership style, work motivation, and work environment, both partially and simultaneously, on the performance of teachers and employees. The research method used is a quantitative survey with a causality approach. The research sample was selected using the stratified random sampling method, and data were analyzed using the SPSS (Statistical Package for Social Science) program, including t-tests and F-tests. The results show that partially, leadership style (t test = 118.636), work motivation (t test = 53.589), and work environment (t test = 159.118) each have a positive and significant influence on the performance of teachers and employees. Simultaneously, leadership style, motivation, and work environment also have a positive and significant influence on performance, as proven by the F-count value of 25.861 being greater than F-table. The conclusion of this study is that a better leadership style, higher work motivation, and a supportive work environment will significantly contribute to the improvement of teacher and employee performance. Keywords: Leadership style, motivation, environmental work and teacher and employee performance